On romance syntactic complex predicates: why Brazilian Portuguese is different (Sobre predicados complexos sintáticos nas línguas românicas: por que o português brasileiro é diferente) - Cyrino, Sonia Maria Lazzarini (Estudos da Língua(gem), 2010)
I analyze clitic climbing as the effect of Romance syntactic complex predicate formation: the non-finite verb phrase moves to the specifier of the upper V. This movement forms a complex predicate so as to allow for a configuration where clitics can climb. Crucial for this movement is the presence of a defective C-T. The lack of clitic climbing in Brazilian Portuguese is but one consequence of a non-defective C-T system in these structures. As a consequence, we have the possibility for certain constructions to occur in the language; in fact, they are presented as additional evidence for the proposal. KEYWORDS: Clitic climbing. Syntactic complex predicates. ECM. Inflected infinitives. Brazilian Portuguese. Principles & Parameters Theory. RESUMO Proponho que a subida de clítico é efeito da formação de predicados complexos sintáticos nas línguas românicas, pois o sintagma do verbo não-finito se move para o especificador do V mais alto nessas construções. Esse movimento forma um predicado complexo, propiciando a subida do clítico. É crucial para tal movimento que haja um sistema C-T defectivo. A falta de subida de clítico no português brasileiro, portanto, é uma conseqüência de um sistema C-T não-defectivo nessas estruturas. Como decorrência, temos a possibilidade de certas construções na língua, que são apresentadas como evidência adicional para a proposta. PALAVRAS-CHAVE: Subida de clítico. Predicados complexos sintáticos. ECM. Infinitivo flexionado. Português Brasileiro. Teoria de Princípios e Parâmetros.